Perancangan Ulang Alokasi Slot Penyimpanan Item Gudang Dengan Metode Class Based Storage Untuk Mengurangi Overtime Pada Warehouse (Studi Kasus PT Sumber Alfaria Trijaya, Tbk/Alfamart Kota Serang) - Fauzan Fadillah; Mohammad Muklis (Prosiding Amal Insani Foundation, 2022)
PT. Sumber Alfaria Trijaya is a company engaged in the retail industry by operating a network of mini markets, under the name "Alfamart". In the distribution process, Alfamart deals with the warehouse as part of the logistics system for storing, receiving and dispensing goods. This research focuses on the warehouse with the highest amount of overtime, which is 11.3%, namely in DC Serang. Through FMEA and Fishbone Diagram analysis, it can be seen that the problem area of overtime that occurs in the warehouse is in the picking area/zone, namely the repack problem during the search process and the difficulty of finding a display location by the picker. Based on the results of the calculation of the existing warehouse throughput, the distance traveled by the picker in the picking area is 11,591.86 meters. The Class Based Storage method with the ABC classification technique serves to classify based on the throughput percentage rating, from the highest cumulative value to the lowest cumulative value. With the proposed layout that has been made, it has resulted in a decrease in the total mileage of 24% by 8,788.02 meters showing a difference of 2,803.84.